2022
DOI: 10.3389/fonc.2022.929012
|View full text |Cite
|
Sign up to set email alerts
|

Novel Agents For Relapsed and Refractory Classical Hodgkin Lymphoma: A Review

Abstract: Classical Hodgkin lymphoma (cHL) is the most common type of HL that occurs mainly in people aged between 15–30 and over 55 years. Although its general prognosis is favorable, 10%–30% of patients with cHL will ultimately develop relapsed or refractory disease (r/r cHL). Improving the cure rate of r/r cHL has proven to be challenging. Some novel agents, such as brentuximab vedotin and immune checkpoint inhibitors, which have been used in conventional regimens for patients with r/r cHL in the past decade, have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 84 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…While several data on PD-1 blockade in DLBCL-type RS are available, the literature describing this treatment strategy applied to HL-type RS is particularly scarce. Since pembrolizumab has shown notable efficacy in the treatment of de novo R/R HL, a potential therapeutic approach may be represented by this drug [115]. Even though the KEYNOTE-170 (NCT02576990) phase II trial enrolled only two R/R HL-type RS patients, it reported promising efficacy outcomes, with an ORR of 100% (one patient reached a CR and the other achieved a PR) [116].…”
Section: Immune Checkpoint Blockadementioning
confidence: 99%
See 1 more Smart Citation
“…While several data on PD-1 blockade in DLBCL-type RS are available, the literature describing this treatment strategy applied to HL-type RS is particularly scarce. Since pembrolizumab has shown notable efficacy in the treatment of de novo R/R HL, a potential therapeutic approach may be represented by this drug [115]. Even though the KEYNOTE-170 (NCT02576990) phase II trial enrolled only two R/R HL-type RS patients, it reported promising efficacy outcomes, with an ORR of 100% (one patient reached a CR and the other achieved a PR) [116].…”
Section: Immune Checkpoint Blockadementioning
confidence: 99%
“…Brentuximab vedotin, widely used for the treatment of de novo R/R HL, is a paradigmatic example of the conjugation of an anti-CD30 mAb and an anti-microtubular agent, namely monomethyl auristatin E (MMAE) [115,126].…”
Section: Drug Conjugated Antibodiesmentioning
confidence: 99%